Transforming Online Retail: The Impact of Augmented and Virtual Reality on Consumer Engagement and Experience in E-Commerce - Cunha, Maria Nascimento; Krupskyi, Oleksandr P. (Current Progress in Arts and Social Studies Research Vol. 10, 2025)
This study investigates the transformative role of augmented reality (AR) and virtual reality (VR) technologies in e-commerce and digital marketing. It aims to understand how these immersive technologies enhance consumer experiences by addressing challenges like product visualization, consumer trust, and engagement while fostering higher purchase intent and customer satisfaction. A systematic literature review synthesizes findings from empirical and theoretical studies published between 2011 and 2024. The methodologies analyzed include experimental designs, market analyses, and conceptual frameworks assessing the integration of AR and VR technologies in online retail. The findings indicate that AR enhances online shopping through features such as virtual try-ons and spatial placement visualization, reducing return rates and increasing purchase confidence. Conversely, VR provides immersive environments that simulate physical shopping experiences, strengthening consumer-brand connections. While AR demonstrates broader applicability in fostering interactive and personalized experiences, VR remains limited by accessibility and cost constraints. Both technologies exhibit immediate costs but offer long-term benefits, positively influencing conversion rates and customer loyalty. This study contributes to consumer behavior research by applying value perception models, immersive technology frameworks, and engagement metrics to the e-commerce landscape. It refines existing theoretical perspectives on technological adoption by highlighting the interplay between sensory engagement, emotional connection, and consumer decision-making. The research underscores the strategic importance of integrating AR and VR into digital marketing and e-commerce platforms. It suggests leveraging AR for product categories requiring spatial interaction and using VR for high-detail product exploration. The study provides actionable insights for businesses looking to enhance online shopping experiences through immersive technologies. This study offers a comprehensive synthesis of AR and VR applications in e-commerce, highlighting their potential to reshape online shopping. Bridging the gap between physical and digital retail experiences provides a fresh perspective on how immersive technologies can drive engagement, accessibility, and personalized consumer interactions. While this study synthesizes existing literature, empirical validation through longitudinal studies and cross-industry applications is necessary. Future research should explore the long-term effects of AR and VR adoption on consumer trust, loyalty, and behavioral changes. Additionally, further exploration is encouraged into gamification, artificial intelligence (AI) integration, and demographic-specific implementations to drive sustainable engagement.